IMPLEMENTATION OF RISK BASED INTERNAL AUDITING IN LANGKAT REGENCY - Yunus, Muhammad (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to determine the effect of the role of the internal auditor, top management commitment, communication processes and training on the implementation of RBIA (Risk Based Internal Auditor) in the Langkat Regency Government. This type of research is causal associative research that uses a quantitative approach. This research was conducted in the Langkat Regency Government. Data collection methods used were questionnaire methods given to research respondents. The type of data used in this study is primary data as primary data and secondary data for additional data. The data analysis method used is using Structural Equation Modeling (SEM). And data processing in this study was carried out with the help of SmartPLS software. The results obtained in this study indicate that training is the most dominant factor in influencing the implementation of Risk Based Internal Auditors in Langkat Regency. It is also known that partially the role of internal auditors and the communication process also has a significant influence on RBIA in Langkat Regency. While the variable of top management commitment cannot influence the implementation of RBIA in Langkat Regency at a significance level of 5%.